2018
DOI: 10.12932/ap-151117-0197
|View full text |Cite
|
Sign up to set email alerts
|

Natural course and prognostic factors of chronic urticaria in Korean children: A single center experience

Abstract: Background: Chronic urticaria (CU) has an adverse effect on academic achievement and psychosocial development in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
3
5
2
Order By: Relevance
“…25 Other recent local studies reported the median onset age of CU to be approximately 4–5 years. 21 26 In the present study, the median age of patients at diagnosis was 5–6 years, similar to recent findings. 21 26 In our study, CU cases were not correlated with age or prognosis, similar to other reports.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…25 Other recent local studies reported the median onset age of CU to be approximately 4–5 years. 21 26 In the present study, the median age of patients at diagnosis was 5–6 years, similar to recent findings. 21 26 In our study, CU cases were not correlated with age or prognosis, similar to other reports.…”
Section: Discussionsupporting
confidence: 92%
“… 21 26 In the present study, the median age of patients at diagnosis was 5–6 years, similar to recent findings. 21 26 In our study, CU cases were not correlated with age or prognosis, similar to other reports. 21 22 26 However, another study showed a higher remission rate in children below 8 years of age than those in older than 8 years 27 ; the remission rate was also higher in children below the age of 10 years.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations